Peningkatan Kemampuan Guru Praktik Produktif Tata Busana dalam Membuat Produk Batik Melalui Workshop kekhasan Wilayah Ngawen, Gunungkidul di SMK Negeri 1 Ngawen - S Supiningsih (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
This study aims to improve the competence of Dress Design teachers in producing batik products through the Ngawen Distinctiveness Workshop at SMK Negeri 1 Ngawen in the Odd Semester of the 2021/2022 Academic Year. The research subjects were 15 productive teachers of Fashion Design at SMKN 1 Ngawen. The object of research is the process of making Ngawen batik through a Ngawen workshop. This research method is School Action Research using two cycles. Data collection techniques using observation and documentation. The result of the research is the application of a workshop that is unique to the Ngawen area to improve the ability of the Productive Practice Teacher of Dressing as indicated by the number of teachers' abilities seen from the teachers who produce products. As well as the number of users and orders of Batik, the initial condition was 5 teachers of Clothing Design to 72 teachers at SMKN 1 Ngawen. Before and before the workshop, judging from its ability, the improvement was very satisfactory, namely 80%.